Evaluation of Ascitic Fluid Cytology in a Tertiary Hospital in South-Western Nigeria: A 7-year Retrospective Study - Oluwatosin O. Oguntoye; Oluwafunmilayo A. Oguntoye; Olawale M. Adeniyi; Oluwadamilola Gideon Osasona; Precious E. Nkereuwem (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: Ascites is the pathological accumulation of fluid within the peritoneal cavity of varied etiology. Various abnormalities can be detected through cytological analysis of ascitic fluid. Ascitic fluid cytology (AFC) is a rapid and cost-effective means of evaluating ascites to establish its nature and cause. Aim: To evaluate ascitic fluid cytological findings over a seven-year period and to correlate the cytological features with the clinical profile of the patients. Materials and Methods: This was an observational retrospective study conducted in a healthcare facility in south-western Nigeria. The reports of AFC tests performed from January 1, 2016 to December 31, 2022 were retrieved to obtain the following information for analysis: Age, Gender, Tribe, Year of the test, Provisional diagnosis, and Cytological diagnosis. Results: The data of a total number of 121 patients were analyzed; 61 males (50.4%) and 60 females (49.6%) with a mean (±SD) age of 51.51 ± 15.22. Decompensated cirrhosis was the commonest clinical diagnosis 65 (53.7%) followed by hepatocellular carcinoma 11 (9.1%). Ascitic fluid cytological findings showed 45 (37.2%) were positive for malignant cells; 46 (38.0%) were negative for malignant cells; 13 (10.7%) were suspicious for malignancy; 9 (7.4%) were acellular smears; and 8 (6.6%) were inflammatory smears. The ascitic fluid of only 4 out of 11 patients with hepatocellular carcinoma tested positive for malignant cells, giving a sensitivity of 36.4%. Conclusion: AFC remains very useful in the diagnostic work-up of patients with ascites but should not be completely relied upon in confirming a malignancy, other additional diagnostic investigations should be deployed.